Influence of protein and vitamin B2 as nutrients of chicken meat on staphylococcal enterotoxin genes expression via virulence regulators. (August 2019) - Wang, Huawei; Cai, Linlin; Wang, Huhu; Xu, Xinglian; Zhou, Guanghong
Abstract: Various food-related stress and intracellular regulators have been previously demonstrated the influence on enterotoxin genes expression, detail information about specific meat nutritional factors promoting enterotoxin genes expression via intracellular regulators still remain unclear. In this study, protein and vitamin B2 as representative nutrients of chicken meat were employed for this preliminary exploration, supplement of protein or vitamin B2 for TSB medium was performed as cultivation in vitro to mimic the contents of protein or vitamin B2 of chicken meat respectively, cell population, virulence regulators and enterotoxin genes expression were determined so as to seek the potential relationship. As a result, there were no significant influences of protein and vitamin B2 on cell growth for four enterotoxigenic Staphylococcus aureus strains, however, various genetic expressing trends were observed within growth cycle, in general, with the comparison of protein and TSB groups, vitamin B2 had universally significant promotion on seb, sec and sed expression, and different strains exhibited varied regulatory preference for enterotoxin genes expression. These results indicated that vitamin B2 is a critical nutritional factor of meat promote enterotoxin genes expression, furthermore, it would provide a new insight into repressing enterotoxin genes expression on the aspect of extracellular nutritional factor. Highlights: Supplements of protein and vitamin B2 had negative effects on S. aureus growth. Vitamin B2 had significant promotion on seb, sec and sed expression. Different strains had various preference to regulate enterotoxin genes expression.